The Dynamics of Islamic Civilization and the Formation of Islamic Educational Thought in the Kingdom of Banjar Through the Role of Sheikh Muhammad Arsyad Al-Banjari - Moh Syaikhol Hadi; M Bahru Wahyuning Aji; Dzulkifli Hadi Imawan (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
This article examines the dynamics of Islamic civilization and the formation of Islamic educational thought in the Banjar Sultanate during the seventeenth to eighteenth centuries, with a particular focus on the role of Shaykh Muhammad Arsyad al-Banjari as a central intellectual figure. This study is significant because previous research has largely emphasized political aspects and Islamic propagation in Banjar, while the dimensions of Islamic educational thought and practice within the context of local civilization have received relatively limited scholarly attention. The study aims to analyze the interrelationship between the process of Islamization, power structures, and the development of Islamic education, as well as to elucidate the contribution of Shaykh Muhammad Arsyad al-Banjari in shaping scholarly traditions and Islamic education in Banjar. This research employs a qualitative approach using library research, with content analysis applied to the works of Shaykh Muhammad Arsyad al-Banjari, particularly Sabilal Muhtadin, alongside historical sources and relevant academic studies. The findings indicate that Islamic education in the Banjar Sultanate developed organically through institutions such as mosques, prayer halls (langgar), and pesantren, supported by a harmonious relationship between religious scholars and political authorities. Shaykh Muhammad Arsyad al-Banjari played a significant role in establishing an integrative paradigm of Islamic education that combined knowledge, moral conduct (adab), and social practice, thereby positioning education as a foundation for the formation of religious character and local Islamic civilization.